QoS Analysis for Cloud-Based IoT Data Using Multicriteria-Based Optimization Approach. (7th September 2022) - Jayakumar, L.; Chitra, R. Jothi; Sivasankari, J.; Vidhya, S.; Alimzhanova, Laura; Kazbekova, Gulnur; Kulambayev, Bakhytzhan; Kostangeldinova, Alma; Devi, S.; Teressa, Dawit Mamiru
Abstract : This work explains why and how QoS modeling has been used within a multicriteria optimization approach. The parameters and metrics defined are intended to provide a broader and, at the same time, more precise analysis of the issues highlighted in the work dedicated to placement algorithms in the cloud. In order to find the optimal solution to a placement problem which is impractical in polynomial time, as in more particular cases, meta-heuristics more or less approaching the optimal solution are used in order to obtain a satisfactory solution. First, a model by a genetic algorithm is proposed. This genetic algorithm dedicated to the problem of placing virtual machines in the cloud has been implemented in two different versions. The former only considers elementary services, while the latter uses compound services. These two versions of the genetic algorithm are presented, and also, two greedy algorithms, round-robin and best-fit sorted, were used in order to allow a comparison with the genetic algorithm. The characteristics of these two algorithms are presented.